Determinant of micro, small and medium enterprises on carrying out a credit loan in Jambi Province - Etik Umiyati; Amri Amir; Haryadi Haryadi; Zulfanetti Zulfanetti (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
This study aims to analyze the determinant of micro, small and medium enterprises (MSMEs) on carrying out a credit loan. Primary data has been used in the analysis. The population in this study were all MSMEs in Jambi Province. Samples were taken by purposive random sampling. Total sample are 276 consisting of 163 MSMEs actors who took credit and 113 MSMEs actors who did not take credits. To analyze the factors that influence the taking of credits, a binary logit model is used. The dependent variable is the taking of credits, while the independent variables are household characteristics and individual characteristics of MSMEs actors. The results showed that the factors significantly affected the MSMEs on taking credit were the side job variables, working hours, working partners, gender, education, long established business, household expenses and account ownership.